Archaeological reconnaissance at Lake E5 in the Brooks Range, Alaska and implications for the early human biomarker record of Beringia. (15th June 2022) - Goebel, Ted; Hoffecker, John F.; Graf, Kelly E.; Vachula, Richard S.
Abstract: Biomarker data from two lakes in arctic Alaska suggest the presence of humans as early as 34, 000 calendar years ago. During July 2021 we conducted an archaeological reconnaissance of one of these lakes: Lake E5 in the Kuparuk River Valley (northeastern Brooks Range), which formed on pre-Wisconsinan glacial till deposits. Our field reconnaissance entailed (1) examination of areas of high ground-surface visibility around the lake; (2) identification of geological contexts of late Pleistocene age; and (3) excavation of 1-m 2 test pits in topographic and geomorphic settings with high potential for human occupation and preservation of archaeological traces of occupation in buried context. Results were unequivocally negative. We found no prehistoric archaeological materials in the lake's basin, from either surface or sampled subsurface contexts. We also found no obvious landforms to target if a search for preserved archaeological contexts continues. The negative results may reflect a false human signal in the biomarker data, possibly due to taphonomic factors (e.g., microbially-mediated degradation of sterol precursors) or low archaeological visibility of a human presence in this setting (i.e., small lake and basin). Highlights: Biomarkers from Lake E5 and Burial Lake in arctic Alaska suggest the possible presence of humans ∼34, 000–19, 000 years ago. An archaeological reconnaissance at Lake E5 in July 2021 failed to yield any traces of human occupation. Results may reflect a false human signal in the biomarker data or low archaeological visibility of human occupation.